2024
DOI: 10.1177/10497323241234482
|View full text |Cite
|
Sign up to set email alerts
|

Mpox Illness Narratives: Stigmatising Care and Recovery During and After an Emergency Outbreak

Anthony K. J. Smith,
Daniel Storer,
Kari Lancaster
et al.

Abstract: In May 2022, a global outbreak of mpox (formerly monkeypox virus) affected thousands of mainly gay and bisexual men. Mpox is usually a time-limited illness that can involve fever, pain, and skin lesions, but may require hospitalisation. There is scant research into the firsthand experiences of people affected by mpox, including experiences of symptoms, healthcare, and recovery. This study considers the different illness narratives of people who experienced mpox in Australia in 2022. In-depth interviews and 6-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…After screening, four qualitative interview-based studies were found to have addressed the question: ‘What are the views and experiences of interventions to prevent sexual transmission of mpox among communities at risk of infection?’ Study characteristics for three cross-sectional [ 32–34 ] and one longitudinal [ 35 ] are given in Table 3 . Two European studies collected data in the initial phases of the outbreak [ 33 , 34 ]; one study in Australia was conducted after the initial outbreak [ 35 ]; and one in China was conducted at a time when reported cases were still increasing [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After screening, four qualitative interview-based studies were found to have addressed the question: ‘What are the views and experiences of interventions to prevent sexual transmission of mpox among communities at risk of infection?’ Study characteristics for three cross-sectional [ 32–34 ] and one longitudinal [ 35 ] are given in Table 3 . Two European studies collected data in the initial phases of the outbreak [ 33 , 34 ]; one study in Australia was conducted after the initial outbreak [ 35 ]; and one in China was conducted at a time when reported cases were still increasing [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies [ 32 , 33 , 35 ] only included men (mostly MSM) with experience of mpox. The fourth study [ 34 ] included only MSM.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations